Dampak Adiksi Media Sosial terhadap Penerimaan Diri dan Kelekatan dalam Relasi Sosial (Adult Attachment) - Dian Misrawati; Rizqi Ria Mariyam; Dina Deviana (Universitas Mercu Buana Jakarta, 2018)
The use of social media is becoming an increasingly widespread trend among millennials. Normal use can provide many benefits for users, but in excessive use up to the stage of addiction can have a negative impact on many aspects of the user's life. This study aims to explore the impact of social media addiction on self-acceptance and attachment style in adult sosial relationship which was conducted in two studies of 488 subjects. Primary data was collected through three research questionnaires. Based on the results of data analysis conducted in the first study, it is known that social media addiction is negatively correlated with self-acceptance (r = 0.326, p = 0,000) and contributes a negative impact of 10.6% to self-acceptance (r2 = 0.106). The results of data analysis in the second study show that social media addiction has an impact on subject’s attachment style to his attachment figure (r = 0.247, p = 0.000). Further analysis with analysis of varians, showed that the fearful attachment style had a significantly higher tendency to social media addiction than the secure, preoccupied and dismissing attachment style (p = 0,000-0,017).